Utilization of High-frequency Mini Probe Ultrasound in the Assessment of Colonic Wall Thickness in Patients With Diverticular Disease. Issue 3 (June 2015) - Kvasnovsky, Charlotte L.; Haji, Amyn; Ryan, Suzanne; Lin, Shu-Ling; Bjarnason, Ingvar; Papagrigoriadis, Savvas
<x xml:space="preserve">Abstract</x> Background: Assessment of diverticular disease (DD) is routinely undertaken by colonoscopy and computed tomography (CT) scan. Improvements in high-frequency ultrasound have enabled evaluation of the colon wall structure in detail. Our objective was to assess ultrasound in measuring colonic wall thickness in DD. Methods: High-frequency 20-MHz ultrasound was undertaken to measure individual layer and total colonic wall thickness. Case patients had symptomatic DD. Control patients underwent colonoscopy for other reasons. Select patients also underwent abdominal CT scan. Results: Thirty-three patients underwent colonoscopic ultrasound, 18 with sigmoid diverticula and 15 control patients. Total wall thickness was greater in patients with DD, 5.69 mm (1.68) versus 2.61 mm (1.29, P<0.0001). Patients with DD had significant thickening in each individual layer of the colonic wall measured (each P<0.0001). Greatest differences were in the muscularis propria, which was an average of 3.5 times thicker in patients with DD. In patients with DD, the segment of colonic wall measured was also thicker, with average mid-sigmoid thickness of 23.0 mm (SD 9.6 mm). Conclusions: Patients with DD have increased sigmoid thickness when compared with controls, especially the muscularis propria. Unlike CT, ultrasound was also able to identify thickening in the mucosa and submucosa.